TWISTED POUCH SYNDROME - A DIFFICULT TO DIAGNOSE MECHANICAL COMPLICATION OF ILEAL POUCH-ANAL ANASTOMOSIS: OUTCOMES AFTER REDO POUCH PROCEDURES. (21st January 2021) - Holubar, Stefan; Lightner, Amy; Qazi, Taha; Savage, Erica; Ream, Justin; Rieder, Florian; Gordon, Ilyssa; Baker, Mark; Hull, Tracy; Steele, Scott
Abstract: Background: Ileal pouch-anal anastomosis (IPAA) is a technically demanding procedure. Intraoperatively, great care must be taken to assure a straight superior mesenteric axis. Rarely, twisted pouches are inadvertently constructed, resulting in deviations of expected pouch function, i.e. patients readily able to open their bowels on average 7x/24 hours without pain. Twisted pouches may result in symptoms classified as pouch dysfunction. Herein we describe our quaternary pouch referral center experience with twisted pouch syndrome (TPS). Methods: We performed a retrospective review of our prospectively maintained pouch registry from 1995 – 2020. Patients were identified using free-text search of redo IPAA operative reports for variations of the term "twist". We defined twisted pouch syndrome as intraoperative findings of twisting of the pouch as the primary pathology. Data are presented as frequency (proportion) or median (interquartile range). Results: Over 25-years, we identified 29 patients with confirmed TPS who underwent a redo pouch procedure by 10 surgeons. Overall, 65% were female, median BMI 21.2 (19.5 – 26) kg/m 2 . The duration from the index IPAA to the redo procedure was 4 (2 – 8) years; all (100%) were referral cases constructed elsewhere. Original diagnoses included: ulcerative colitis (90%), FAP (10%), lack of interstitial cells of Cajal in 1 patient (10%). All patients presented with symptoms of pouch dysfunction including erratic bowel habits (96%) with urgency/frequency, abdominal/pelvic/rectal pain (92%), and obstructive symptoms (88%). Most had (75%) been treated for chronic pouchitis with antibiotics or biologics, and 46% had undergone 1 or more additional surgery. Prior to redo IPAA procedure patients underwent a thorough workup: 100% pouchoscopy, 96% GGE, 93% underwent EUA, 88% MRI, 73% manometry, and 42% defecography. TPS was diagnosed in 15% by pouchoscopy, in 10% by imaging, and in 75% was diagnosed intra-operatively at re-diversion (20%) or revision/redo IPAA (55%). In terms of surgical intervention, 85% were initially re-diverted. A total of 18 (62%) underwent pouch revision, and 10 (38%) required redo-IPAA. Short-term outcomes: LOS 7.5 (5 – 9) days, any complication 48%, readmission 11%, reoperation 3.4%, zero mortalities. After a median follow-up 50 (28 – 60) months, 2 never had loop ileostomy closure, 1 had pouch excision, and 1 a Kock pouch, yielding an overall pouch survival rate of 86%. Conclusions: Twisted pouch syndrome presents with pouch dysfunction manifest by erratic bowel habits, unexplained pain, and obstructive (defecation) symptoms. This syndrome may also mimic chronic pouchitis. Despite a thorough workup which may suggest a mechanical problem, many patient may not be diagnosed until time of redo pouch surgery. Redo surgery for twisted pouch syndrome results in long-term pouch survival for the majority.